Attunement and Affordance Learning in Infants - De Bordes, Pieter F.; Hasselman, Fred; Cox, Ralf F. A. (Journal of cognition and development, 2019)
From a perceptual learning perspective, infants use social information (like gaze direction) in a similar way as other information in our physical environment (like object movements) to specify action possibilities. In the current study, we assumed that infants are able to learn an affordance upon observing an adult failing to act out that affordance, without appreciating object-directed intentions, or, communicative intent towards the infant. Using a variation of the Re-enactment procedure, we found that when the attention of infants (N = 46, M age = 20 months) was drawn towards the eyes of the person before she acted out the failed attempt, either by ostensive cues or non-ostensive cues, infants achieved more affordances than when their attention was not directed towards the eyes. As directing the attention of infants to the eyes of another person frequently results in gaze following, this suggests that infants use the gaze direction of another person in order to learn what affordance that other person is trying to realize. In addition, the results of a spatiotemporal analysis on the eye-movements of infants suggest that the gaze and the object movements of the person facilitate learning by directing the attention of infants towards important object-directed actions on crucial moments during the failed attempt demonstrations. These results are discussed in terms of perceptual attunement and affordance learning.